JARINGAN KOMUNIKASI PETANI DALAM ADOPSI INOVASI PERTANIAN TANAMAN PANGAN DI DESA REJO BINANGUN KECAMATAN RAMAN UTARA KABUPATEN LAMPUNG TIMUR - Audina Meutiara; Indah Nurmayasari; Rio Tedi Prayitno (Lampung University, 2017)
This study aims to analyze the level of food crop agriculture adoption-inovation and the relationship between communication networks and the level of the adoption-inovation. The location of this study was chosen puposively in Rejo Binangun village, Raman Utara subdistrict, East Lampung regency. Respondents of this research are 34 farmers. Data were collected in March-May 2016. The research used a survey method with qualitative and quantitative analysis and used nonparametric statistics test Rank Spearman correlation to test the hypothesis. The results of this research showed that the level of foodcrop agriculture adoption-inovation involving rice and cassava in Rejo Binangun village, Raman Utara subdistrict, East Lampung regency is in medium classification and the level of food crop agriculture adoption-inovation has a significant correlation to the level of diversity of communication networks in Rejo Binangun village, Raman Utara subdistrict, East Lampung regency. Keywords: adoption-inovation, communication networks, food crop agriculture